Persuasion Speech Analysis in Xi Jinping's Speech during the National Day Celebration of the People's Republic of China - Adam Galih Waskita Putra Simanungkalit; T. Kasa Rullah Adha; Muhammad Yusuf (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
Communist countries often utilize persuasive speech to demonstrate authority, leadership, and legitimacy of the ruling party. This study explores the use of persuasive utterances delivered by the president of the People's Republic of China, Xi Jinping, during the People's Republic of China National Day celebration. This qualitative study is based on data from Xi Jinping's speeches during the National Day Celebrations of the People's Republic of China during Xi Jinping's tenure. The data are in the form of sentences that have elements of persuasion, which were collected using content analysis techniques. The findings of this study are that 46 persuasion utterances were found in four speech texts of Xi Jinping. The persuasion sentences vary, but always follow the following indication patterns, namely (1) the use of collective pronoun, (2) the use of collective nouns, (3) the use of deontic modality, (4) the use of epistemic modality, (5) the use of majas, and (6) the use of evaluative vocabulary.